THE INFLUENCE OF TELEPRESENCE, SOCIAL PRESENCE, AND SOCIAL VALUE ON REPURCHASE INTENTION OF ONLINE VIRTUAL GAME ITEMS - Al Ayyubi, Sholahudin Aditya; Yuliati, Lilik Noor (Journal of Child, Family, and Consumer Studies, 2024)
The emergence of online learning during the COVID-19 pandemic has led to an increase in the use of gadgets by students. The increasingly proficient use of gadgets for teenagers is not only used for learning activities but also for playing online games. This study aims to identify consumer characteristics and influences, telepresence, social presence, social value, and repurchase intention of online game virtual items in adolescents and analyze the relationship between consumer characteristics and repurchase intention of online game virtual items in adolescents. This study involved 239 adolescents who were dominated by males and were in the late adolescent stage with an age range between 19-24 years. The last education of the majority of respondents is high school graduates, and the monthly allowance of most respondents is above Rp1.000.000. Telepresence, social presence, and social value variables are in the medium category, which means they are pretty good. However, the repurchase intention variable is in the low category, meaning the interest in repurchasing online game items is relatively low. Based on the influence test, it can be concluded that telepresence and social value variable has significant effect on repurchase intention.